Entrepreneurship Venture Creation Among Nigerian Graduates: Effects Of Perceptive Factors, Enterprising Attributes, And Entrepreneurship Education On Entrepreneurial Capabilities - Na Allah, Shehu Rabiah (2023)
This study investigated the phenomena of over-reliance on hired jobs that has discouraged most Nigerian graduates from becoming entrepreneurs after graduation. As a result, prompting the economy into problems of unemployment, poverty and low economic growth that threatens security challenges. Drawing the research on the formative basis, it analyzed the mediating role of entrepreneurial dynamic capabilities (ENTCP) and moderating effect of entrepreneurial support (ENTSP) on the relationship between perceptive factors (PF; self-efficacy, outcome expectations, entrepreneurial interest, choice goal), enterprising attributes (EA; innovativeness, risk-taking, proactiveness, autonomy, competitive aggressiveness) and entrepreneurship education (EED; learning, inspiration, incubation resource) on entrepreneurship venture creation (EVC) among Nigerian graduates.